Development of the respiratory tract microbiota in cystic fibrosis. Issue 6 (November 2016) - de Koff, Emma M.; Groot, Karin M. de Winter-de; Bogaert, Debby
Abstract : Purpose of review: Progression of lung disease in cystic fibrosis (CF) is punctuated by Pseudomonas aeruginosa infection and recurrent pulmonary exacerbations, and is the major determinant of a patient's life expectancy. With the advent of novel deep-sequencing techniques, polymicrobial bacterial assemblages rather than single pathogens seem to be responsible for the deterioration of pulmonary function. This review summarizes recent insights into the development of the CF respiratory tract microbiome, with its determinants and its relations to clinical parameters. Recent findings: Research has moved from microbiota snapshots to intensive sampling over time, in an attempt to identify biomarkers of progression of CF lung disease. The developing respiratory tract microbiota in CF is perturbed by various endogenous and exogenous factors from the first months of life on. This work has revealed that both major pathogens such as P. aeruginosa and newly discovered players such as anaerobic species seem to contribute to CF lung disease. However, their interrelations remain to be unraveled. Summary: Long-term follow-up of microbiome development and alterations in relation to progression of lung disease and treatment is recommended. Moreover, integrating this information with other systems such as the metabolome, genome, mycome and virome is likely to contribute significantly to insights into host–microbiome interactions and thereby CF lung disease pathogenesis.